Imunohistoquímica em órgãos de tilápias-do-Nilo imunizadas com antígeno insolúvel de Streptococcus agalactiae - Marcusso, Paulo Fernandes [UNESP] (2015)
The infection caused by Streptococcus agalactiae causes heavy losses in intensive farming of tilapia systems in Brazil and one of the solutions to minimize these losses is the use of vaccines. Thus, this study evaluated the tag from the cells by immunohistochemistry Ig M antibody responses and participate in the kidney, spleen and liver in the humoral immune response induced by the vaccine against S. agalactiae. Therefore, we analyzed 166 of the tilapia (Oreochromis niloticus) with an average weight of 200 ± 25 g. It determined the bacterial concentration lethal to 50.0% of the fish (LD50) 40 tilapias used medium 4 distributed in 250 L glass fiber boxes 10 animals. The animals were inoculated with increasing doses of S. agalactiae (1x102, 1x104, 1x106 and 1x108), getting the LD50 estimated at 1x107,71 and the lower and upper limit in 1x106,52 and 1x107,98 respectively. Later the test was carried out to collect the bodies for subsequent histological and immunohistochemical evaluation. Therefore, we used two groups (n = 63), namely; group injected with 200 uL saline 0.65% (control) and group immunized with the vaccine containing the insoluble portion of the product of sonication S. agalactiae added to Freund's incomplete adjuvant (1:1) with final volume of 200 uL. The vaccine and saline were applied via intracelomic (i.c) and in all the groups were made to collect the pre immunization organs and graded post immunization collected on days 7, 14, 21, 28, 35, 42, 60 and 90 days to evaluate the dynamics of humoral immune response by immunohistochemistry with the Ig M antibody and histological evaluation in the coloring hematoxilia and eosin. The results were compared using analysis of variance (ANOVA) at 5% probability and the difference between the means were compared by Tukey test. Immunization of the Nile tilapia with S. agalactiae insoluble antigen-induced proliferation of splenic lymphocytes, leading to significant increases in ...